EFEKTIVITAS PROGRAM BANTUAN PANGAN BERAS MISKIN (RASKIN) DI DESA PANDANREJO KECAMATAN BUMIAJI KOTA BATU - Virani Saputri Sanja; Roro Merry Chornelia; Annisa Purwatiningsih (ADMIN: Jurnal Administrasi Negara, 2026)
The effectiveness of the Rice Food Assistance Program for the Poor (Raskin) in Pandanrejo Village, Bumiaji District, Batu City, was evaluated in this study using a descriptive qualitative methodology. Unstructured interviews, documentation, and observation were used to gather data. The village head, village secretary, government officials, hamlet head, and three locals were among the purposefully chosen informants. Technical triangulation was used to assess the validity of the data, and the Miles and Huberman interactive model was used to analyse the data at each stage: collection, reduction, presentation, and conclusion drawing. The outcomes demonstrated that, with the assistance of qualified village authorities and sufficient facilities, the Raskin Program was effective, well-organised, and on course. The primary enablers were the officers' cooperation and coordination, but distribution delays and inclement weather posed challenges. Although this programme helps impoverished people satisfy their dietary requirements, it has to be evaluated often to maximise its effectiveness.